Counteracting Hoax in Social Media Through Tabayyun By Islamic Student Community - Iredho Fani Reza (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study aims to find out hoaxes on social media and how the form of tabayyun and its implementation can be a method of preventing hoaxes spread on social media. Using this type of research mixed methods with the design of the Sequential Exploratory Strategy. The subjects in this study N Total = 514 who were Muslim students at universities in Palembang City which were determined using purposive sampling technique. The data collection method used an online survey. Data analysis using coding techniques (open coding, axial coding and selective coding) version 9 of the Atlas.ti program and product moment analysis and testing for level categorization of the IBM SPSS version 24 program. This study found, first, the form of hoaxes on social media: 1) News lie; 2) False information; 3) Does not match the facts. Second, students have not implemented tabayyun optimally in responding to news on social media. The form of the application of tabayyun is to seek the truth by thinking critically, observing and confirming the news and information obtained.